Landscape as Operational Notion in the Performing Arts - Schuquel, Maurílio Bertazzo (Revista Brasileira de Estudos da Presença, 2021)
This essay aims to trigger the landscape as an operational notion in the Performing Arts. It reflects the landscape of Gertrude Stein theater as a paradigm for a scene architected from a co-relational way. It appears, that the landscape as an exemplary condition can operate as a theatrical poetic perceived in its entirety, in its materializations and in its possible imaginary senses.